1981
DOI: 10.1530/jrf.0.0620423
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the removal of the various accessory sex glands on the fertility of male rats

Abstract: Summary. Accessory sex glands were removed from rats which were then allowed to mate with females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 8 publications
2
59
0
3
Order By: Relevance
“…The process of insemination is no longer viewed simply as the delivery of sperm into the female reproductive tract [1]. Although this might be the primary purpose of insemination, there is now evidence that semen can act directly on tissues in the female reproductive tract to elicit accessory functions which in turn may influence implantation, development of the pre-implantation embryo and future health of the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The process of insemination is no longer viewed simply as the delivery of sperm into the female reproductive tract [1]. Although this might be the primary purpose of insemination, there is now evidence that semen can act directly on tissues in the female reproductive tract to elicit accessory functions which in turn may influence implantation, development of the pre-implantation embryo and future health of the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory results about the effect of this binding have been shown, such as inducing capacitation of rat sperm (Manco and Abrescia, 1988;Metafora et al, 1988;Peitz 1988) and suppressing capacitation of mouse sperm (Huang et al, 2000). Furthermore, the removal of the seminal vesicles of several species induced complete infertility (Davis and Niwa, 1974;Queen et al, 1981;Peitz and Olds-Clarke, 1986), greatly decreased the pregnancy rate and litter size of mouse (Pang et al, 1979), and induced a decreased motility of uterine sperm and pregnancy rate (Peitz and Olds-Clarke, 1986). These results indicate the important role of SVS in mammalian sperm function.…”
mentioning
confidence: 99%
“…Little is known about the role of SVS in male reproduction, but it has been reported that the removal of the seminal vesicles leads to reduced fertility (Pang et al, 1979;Queen et al, 1981 ;Peitz and Olds-Clarke, 1986). As an ongoing effort to understand the role of Feminal plasma components in reproductive biology, we describe here some molecular properties of the major proteins in mouse seminal vesicular fluid.…”
mentioning
confidence: 99%